A new record of species Didymocarpus kerrii Craib (Gesneriaceae Dumort) for the flora of Vietnam - Xuyen, Do Thi; Phuong, Vu Xuan (Academia Journal of Biology, 2012)
The genus Didymocarpus Wall. comprises about 180 species, mainly distributed Southeast Asia, there were 3 Didymocarpus species recorded in Vietnam. During the study of specimens of Gesneriaceae collected in Vietnam, we found species Didymocarpus kerrii Craib in Ba Vi national park, Vietnam. Didymocarpus kerrii is herbs, have or near stemless. Leaves basal or opposite if have stem, leaf blade near round or broadly elliptic, ca. 1-4.5 × 1-4 cm, papery, pubescent in 2 surfaces especially gladuland hair in abaxial surface, and then glabrous, margins serrate, lateral veins 5-6 pairs; petiole 0.5-5 cm long. Inflorescences cymes, multi-flower; peduncle with puberulent, and then glarous; Calyx connate into campanulate, 5 mm long, 2 lips. Corolla 20 mm long, outer glabrous, 2 lips: adaxial lip 2 lobes; abaxial lip 3 lobes, longer than adaxial lip, round apex. Stamens 2, coherent at the anther; Filament 2 mm long, adnate in middle of corolla, glabrous; ovary 10 mm long, glabrous; style 3-4 mm long; stigma head. Capsule line, straight, ca. 3-4 cm long, glabrous. Seeds unappendaged. This species is closed to D. pulcher but differs from the later by having corolla outer glabrous; leaf blade near round or broadlly elliptic, ca. 1-4,5 × 1-4 cm. Voucher specimens were collected in Ba Vi national park, Hanoi and deposited in the Herbarium of the Institute of Ecology and Biological Resources, Hanoi, Vietnam (HN).